Plasma levels of F-actin and F:G-actin ratio as potential new biomarkers in patients with septic shock. (17th February 2016) - Belsky, Justin B.; Morris, Daniel C.; Bouchebl, Ralph; Filbin, Michael R.; Bobbitt, Kevin R.; Jaehne, Anja K.; Rivers, Emanuel P.
Abstract: Objective : To compare plasma levels of F-actin, G-actin and thymosin beta 4 (TB4) in humans with septic shock, noninfectious systemic inflammatory response syndrome (SIRS) and healthy controls. Results : F-actin was significantly elevated in septic shock as compared with noninfectious SIRS and healthy controls. G-actin levels were greatest in the noninfectious SIRS group but significantly elevated in septic shock as compared with healthy controls. TB4 was not detectable in the septic shock or noninfectious SIRS group above the assay's lowest detection range (78 ng/ml). Conclusions : F-actin is significantly elevated in patients with septic shock as compared with noninfectious SIRS. F-actin and the F:G-actin ratio are potential biomarkers for the diagnosis of septic shock.